2012
DOI: 10.1111/j.2042-3306.2011.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the pharmacokinetics of a fourth generation cephalosporin in three different age groups of New Forest ponies

Abstract: SummaryReasons for performing study: To compare the pharmacokinetics of the fourth generation cephalosporin, cefquinome, in neonatal foals, 6-week-old foals and mature New Forest ponies in order to recommend appropriate dosage regimens for use of this drug. Methods: Cefquinome was administered i.v. at 1 mg/kg bwt twice a day (q. 12 h), 1 mg/kg bwt 3 times a day (q. 8 h) or 4.5 mg/kg bwt q. 12 h to each age group (n = 6). Plasma cefquinome concentrations were analysed using high-performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Where T > MIC (in percent) is the time interval during which the drug plasma concentration is above or equal to the minimal inhibitory concentration (MIC) values; D is the planned dose; t 1/2 the terminal elimination half-life; and t is the dose interval (Smiet et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where T > MIC (in percent) is the time interval during which the drug plasma concentration is above or equal to the minimal inhibitory concentration (MIC) values; D is the planned dose; t 1/2 the terminal elimination half-life; and t is the dose interval (Smiet et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Cefquinome is the fourth generation cephalosporin, mainly used in veterinary medicine. This drug has been developed especially for use in veterinary medicine (Smiet et al, 2012; Papich, 2014), and is registered in many countries worldwide. Cefquinome has been used for the treatment of many diseases including acute mastitis, respiratory diseases, food rot in cattle, calf septicemia, metritis-mastitits-agalactia syndrome in sows, foal septicemia and respiratory diseases in horses (Uney et al, 2011; Liu et al, 2012; Dumka et al, 2013; Shan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The multiple‐dose kinetics of CFQ indicated that the t 1/2 λz ranged from 2.10 h to 2.41 h, which was similar to the previously reported values for CFQ in horses (Allan & Thomas, ; CVMP, ; Winther et al ., ; Smiet et al ., ). The mean MRT values ranged from 1.47 to 2.57 h, which were similar to previously reported values for CFQ in horses (Smiet et al ., ). However, the MRT was slightly shorter than the t 1/2 λz of all dose groups.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have described the pharmacokinetics of CFQ following the i.v. administration of both single (0.5–2 mg/kg, Allan & Thomas, ; CVMP, ; 1 mg/kg, Winther et al ., ; 4.5 mg/kg, Smiet et al ., ) and multiple (a total of 3 doses of 1 mg/kg at 8‐h intervals and 2 doses of 1 mg/kg at 12‐h intervals; Smiet et al ., ) doses in horses. These studies have not reported adverse reactions of horses to CFQ.…”
Section: Discussionmentioning
confidence: 99%
“…Their pharmacokinetics is extensively studied in a number of animal species after different routes of administration. These drugs have a similar distribution and differ mainly in elimination phase and especially in elimination rates depending on the species and age (Smiet et al, 2012). Considerable variations are registered after oral absorption.…”
Section: Introductionmentioning
confidence: 99%